MODEL KEPEMIMPINAN PENDIDIKAN SYEKH NAWAWI AL-BANTANI - Sarmain, Sarmain; Rahman, Zaky Dhiaulhaq; Muslihah, Eneng; Bachtiar, Machdum (STKIP Pesisir Selatan, 2025)
This study discusses the thinking and educational leadership model of Sheikh Nawawi Al-Bantani, one of the great scholars of the archipelago who made an important contribution to the spread of Islam and the development of education. The subject matter of this study highlights the concept of education that emphasizes the balance between science, charity, and morals, as well as its relevance to the challenges of Islamic education in the era of globalization. The purpose of this research is to elaborate on Sheikh Nawawi's pedagogical ideas, including his views on the nature of Islamic education, the purpose of seeking knowledge, learning methods, and the leadership model he inherited. The method used is qualitative research with a descriptive approach through library research. Data were obtained from Sheikh Nawawi's works, previous research, and related literature that were analyzed using a phenomenological approach. This allows the author to reflect on the events and thoughts of Sheikh Nawawi in the context of the implementation of Islamic education. The results of the study show that education according to Sheikh Nawawi is worship as well as a means of social reform based on the Qur'an, hadith, ijma' ulama, and the view of salaf al-salih. His leadership model is characterized by the depth of knowledge, integration of theory and practice, moral example, interactive methods, and fostering a generation of character and independence.